Advances in understanding spontaneous intracerebral hemorrhage: insights from neuroimaging. (June 2014) - Wilson, Duncan; Charidimou, Andreas; Werring, David J
Abstract : Spontaneous (non-traumatic) symptomatic intracerebral hemorrhage is a devastating form of stroke, with very high overall mortality and morbidity. Even with the best current medical or surgical treatment, outcomes still remain poor. By contrast with ischemic stroke, the incidence of intracerebral hemorrhage is not decreasing. Indeed, the incidence of intracerebral hemorrhage related to antithrombotic drugs, including oral anticoagulants, has increased in recent decades. Despite the clear unmet research need for both prevention and acute treatment, there has, until recently, been limited progress in understanding the pathogenesis of this disease. New advances, especially related to neuroimaging biomarkers, are rapidly increasing our understanding of the spectrum of mechanisms of brain injury in intracerebral hemorrhage. The aim of this article is to review recent insights from neuroimaging studies into the pathophysiology and causes of intracerebral hemorrhage, focusing on MRI. We also discuss some of the current and future challenges facing clinicians in understanding and treating intracerebral hemorrhage.